ANALYSIS OF REAL ESTATE RECORDS IN FB&H - Jusuf Topoljak; Zemir Buljubašić (Geodetski Glasnik)
The long-standing tradition of real estate registration in Bosnia and Herzegovina has led to the development of several different models for recording real estate information. From the time of the Ottoman Empire to the present day, various authorities have taken charge, each leaving its own mark on the methods of recording real estate and property rights. This paper examines the current state of cadastral and land registry records in the Federation of B&H, as well as the human resources and geodetic equipment available to municipal and city services. The research findings indicate that changes in laws affecting property record-keeping have had significant impacts, resulting in a highly diverse situation regarding real estate records in the Federation of Bosnia and Herzegovina today. This paper provides an accurate overview of the current state of real estate records and offers a solid foundation for making decisions and planning improvements to the management of property records and rights.